Tonggo and Martonggotonggo in the Traditional Ceremony of the Toba Batak Community - Octavianna, Yessy; Sibarani, Robert; Situmorang, Hamzon; Hasibuan, Nam Syahot (KnE Social Sciences, 2019)
Every ritual in Toba Batak community uses language as a basic tool in its implementation. The verbal forms used in rituals are usually in the form of incantations (tabas) and prayers (tonggo); tabas is spoken by a shaman while tonggo is spoken by partonggo(the leader of a prayer). Tonggo is spoken with the rhythm of the language according to bound speech; its contents are only in the form of requests, praise, confession, and submission to spirits and it is carried out by serving large and small offerings. The martonggo tradition consists of prayers in each religious event, customs and other events, which can provide comfort and kindness in an event or party. The purpose of this paper is to describe (1) the meanings of tonggotonggo in the traditional ceremony of the Toba Batak community and (2) the functions of the martonggo-tonggo tradition in the traditional ceremony of the Toba Batak community. This paper uses an anthropolinguistic approach with the analytic parameters of interconnection, valuability, and sustainability. A qualitative paradigm of ethnography is also used in this study by applying twelve steps in observation and interview methods. The function of the tradition of martonggotonggo for the owner’s community is as the educational tool, as the projection system and as the means of validating culture. The incantation of Tonggotonggo means that humans expect to be able to obtain prosperity in their lives. Keywords: Tonggotonggo, Martonggo-Tonggo, Antropolinguistic